Using the RETAIN Tabletop Simulator as a Summative Assessment Tool for Neonatal Resuscitation Healthcare Professionals: A Pilot Study - Ghoman, Simran K.; Cutumisu, Maria; Schmölzer, Georg M. (Frontiers in Pediatrics, 2020)
Background: Frequent and objective summative assessment of neonatal healthcare providers is important to ensure high-quality care to patients during neonatal resuscitation. Currently, neonatal resuscitation providers are only individually assessed using an at-home online multiple-choice questionnaire. While simulation-based assessment is preferred, resource constraints limit its widespread uptake. An alternative approach to simulation-based summative assessment is needed. Simulation-based serious games may provide a solution. Objective: The aim of this study was to examine if individual performance on the RETAIN (REsuscitation TrAINing for healthcare professionals) tabletop simulator can be used as a summative assessment of neonatal resuscitation providers, regardless of their prior board game experience. Method: Neonatal healthcare providers were recruited from a tertiary perinatal center to complete a (1) demographic pre-survey, (2) neonatal resuscitation scenario using an open-answer written pre-test, (3) neonatal resuscitation scenario using the RETAIN tabletop simulator, and (4) post-survey measuring usage and attitudes toward board games. Multiple linear regression analyses using the Johnson–Neyman technique were conducted in R to probe the moderation effect of years of board game on the relationship between pre-test and game performance. Results: Twenty Neonatal Resuscitation Program-trained healthcare providers (nurses, nurse practitioners, respiratory therapists, and fellows) were recruited for this study (n = 19 females). Participants' mean (standard deviation) pre-test score was 8.35 (1.81) out of a total 16 possible points (52%) and a score of 18 (4.41) out of a total of 40 possible points (45%) using RETAIN. Overall board game experience was 22.5 (12.6) years. Finally, years of board game moderated significantly the relation between the pre-test and game performance (B = −0.13, SE = 0.05, beta = −0.48, t = −2.77, p < 0.05; 95% CI [−0.24, −0.03]). Thus, participants' performance on the two tests (written and simulator) was significantly positively associated, but only for those who reported fewer than 21.5 years of board game experience. Conclusion: This study reports the preliminary results of a pilot study, indicating that the RETAIN tabletop simulator could be used as a simulation-based summative assessment, an enjoyable, low-cost alternative to traditional assessment approaches. RETAIN offers a solution to the need for more frequent and continued assessment of neonatal resuscitation providers.